The Comparative Analysis of Motivation and Student’s Learning Outcomes by Using The Learning Media of Web E-Learning and Schoology in VHS - Aman Maathoba; Tri Rijanto (Faculty of Engineering, Universitas Negeri Yogyakarta, 2022)
This study aims to: (1) find out the comparison of student learning outcomes between the use of learning media of web e-learning and schoology in Web Programming and Mobile Device subjects (WPMD), and (2) find out the increase in student completeness by using the learning media of web e-learning and schoology on WPMD subjects. The research method used is quantitative with quasi-experimental research involving two groups, namely the control and experimental groups. While the research design used was pre-test post-test control group design. The subjects of this study were students of class XII RPL at SMK Negeri 1 Sukorejo. Data collection techniques carried out by providing research instruments and test instruments. While the data analysis technique uses normality test, homogeneity test, and independent samples t-test. The results of this study indicate that: (1) Significant results of 0.000 are smaller than 0.05, which means that learning outcomes in WPMD subjects have significant differences between the control and experimental groups. (2) The results of the study note that the control group experienced an increase in completeness of 11.43% while the experimental group amounted to 94.12%. Increased completeness in the experimental group was higher when compared to the control group.